Sampling and distribution pattern of Trioza erytreae Del Guercio, 1918 (Hemiptera: Triozidae) in citrus orchard. (15th February 2021) - Benhadi‐Marín, Jacinto; Pereira, Luís F.; Rodrigues, Isabel; Fereres, Alberto; Alberto Pereira, José
Abstract: Developing efficient sampling protocols is essential to monitor crop pests. One vector of the citrus disease HLB, the African citrus psyllid Trioza erytreae Del Guercio, 1918 (Hemiptera: Triozidae), currently threatens the lemon industry throughout the Mediterranean region. In this work, a pool of sampling methods devoted to monitoring the population of T. erytreae was compared, its spatial distribution in the orchard was assessed, and the minimum sampling effort for the best sampling method was estimated. Three lemon orchards in North‐western Portugal were sampled for one year using two types of yellow sticky traps (standard yellow and fluorescent Saturn yellow), B‐vac sampling and sweep net sampling. The method that best performed, in terms of cost‐efficiency, was the yellow sticky traps. The two colours of the sticky traps tested did not yield a significantly different number of catches. The spatial distribution throughout the orchards was found to be aggregated towards the borders. A minimum of three sticky traps per hectare was found to be enough to estimate the population at 90% accuracy for the mean during the outbreak. These results should help to monitor and anticipate outbreaks that may even colonize neighbour orchards. Studies on the local dispersion patterns of T. erytreae throughout the orchard are mandatory to further refine and optimize efficient monitoring protocols.